Modification of nanofiller to improve the final properties of polylactic acid(PLA)nanocomposites - Anthony, Latisha (2012)
Modifications of nanoclay were prepared from pristine clays and organoclays with Transition Metal Ions (TMIs),Ferum, Copper and Nickel using different solvents.The first part of the experiment focuses on determining the viability of Ethanol as a solvent in the modification process as well as its efficiency in aiding the adsorption of TMIs in comparison to solvents such as Methanol and Dioxane.The composition and structure of the modified nanoclay were characterized using Atomic Absorption Spectroscopy (AAS), Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy (SEM).From the AAS results,it was determined that Ethanol was a viable solvent for the nanoclay modification and proved to be extremely efficient for Copper ions especially.SEM and FTIR results proved that modified nanoclays had smoother surfaces for pristine clays or montmorilonite(MMT)which proved that the modification was successful.The same modifications performed on organoclayswere proven to be unsuccessful.The modified samples were then intercalated in Polylactic Acid (PLA) polymer matrices to form polymer nanocomposites (PNC).The biodegradability and thermal stability of the Polymer nanocomposites were tested and its performance is compared against a polymer nanocomposite intercalated with pure (unmodified) nanoclay.The PNC were formed using solution intercalation method with 1,4-Dichloroethane as a solvent. Both the biodegradability and thermal stability also showed positive improvements.Biodegradibility is hypothesized to have increased due to the characteristics of transition metal ion which are easily oxidized.The ions with higher electronegativity showed the least improvement when intercalated into the polymer matrices.Thermal stability also increased significantly,due to the transition metal ions hindering the pristine clay within the polymer matrices from decomposing easily.Further research will be required to commercialize findings.